Problem of construction of the concept of "Smart city" - Опірський, Іван Романович; Тютіков, Олег Юрійович (Ukrainian Information Security Research Journal, 2020)
The use of artificial intelligence allows you to automate as much as possible all the processes that control the systems of a smart city. Using such a system eliminates the possibility of unauthorized access to the data of the smart city system through a vulnerable point - the human factor. To build smart city systems, data protection and privacy, it is necessary to develop means of protection against information leakage. There are a number of problems and threats, including one of them - cyber attacks, attacks that can block the movement of cars by switching traffic lights, intercept the signal of private and public cameras, switching networks such as Wi-Fi, 4G / 5G, RFID, GSM and others, block access to the supply of water, gas and electricity to residential buildings. However, smart city systems can improve the level of logistics by installing sensors on the roads, security, installing CCTV cameras in public transport, protecting every purchase or exchange, saving water, gas, electricity and security in the city. This also applies to the general "smart" development of a person who will possess electronic skills. This article reveals the problems and features of creating a system of "smart city". Analysis of the “smart city” systems made it possible to identify the main threats from the point of view of building “smart city” systems - threats to confidentiality, data theft, evil devices, the constant denial of access, the denial of service, the loss of control over resources. An analysis of the threats presented allowed us to introduce methods by which we can secure the systems of the “smart city”. The article also describes the advantages and disadvantages of such systems. The analysis of financial distribution from the side of the state and private organizations for the construction of smart city systems was carried out. The basic concepts for building new systems of the “smart city”, in particular, the place of artificial intelligence in them are given. The analysis carried out in the article showed that modern society needs innovative technological solutions so that urbanization can continue in a safe, efficient and healthy way for us and the planet. The combination of AI, sensors, cloud computing, working hand in hand, with clear privacy laws and a strict definition of human rights, will give us truly smart cities that can serve as the basis for human growth and prosperity.